2011
DOI: 10.1038/onc.2011.425
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia and MITF control metastatic behaviour in mouse and human melanoma cells

Abstract: Melanomas are very aggressive neoplasms with notorious resistance to therapeutics. It was recently proposed that the remarkable phenotypic plasticity of melanoma cells allows for the rapid development of both resistance to chemotherapeutic drugs and invasive properties. Indeed, the capacity of melanoma cells to form distant metastases is the main cause of mortality in melanoma patients. Therefore, the identification of the mechanism controlling melanoma phenotype is of paramount importance. In the present repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
189
4
3

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 163 publications
(212 citation statements)
references
References 40 publications
16
189
4
3
Order By: Relevance
“…28,29 It is reported that HIF-1a can activate CXCR4, PDK1 to promote the invasion and metastasis of melanoma cells. 30,31 In addition, bcl -2 plays an important role in promotion of melanoma angiogenesis. 31,32 After overexpression or inhibition of miR-33a, we tested HIF-1a expression and found it had an opposite trend of miR-33a, which highly suggested it may be a target gene of miR-33a.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…28,29 It is reported that HIF-1a can activate CXCR4, PDK1 to promote the invasion and metastasis of melanoma cells. 30,31 In addition, bcl -2 plays an important role in promotion of melanoma angiogenesis. 31,32 After overexpression or inhibition of miR-33a, we tested HIF-1a expression and found it had an opposite trend of miR-33a, which highly suggested it may be a target gene of miR-33a.…”
Section: Discussionmentioning
confidence: 99%
“…30,31 In addition, bcl -2 plays an important role in promotion of melanoma angiogenesis. 31,32 After overexpression or inhibition of miR-33a, we tested HIF-1a expression and found it had an opposite trend of miR-33a, which highly suggested it may be a target gene of miR-33a. To further confirm that HIF-1a is the direct target of miR-33a, we performed dual luciferase reporter assay which testify that miR-33a has a direct binding at HIF-1a 3'-UTR.…”
Section: Discussionmentioning
confidence: 99%
“…Two other lung alveolar differentiation transcription factors (GATA6 and HOPX) also cooperatively limit the metastatic competence of lung adenocarcinoma (Cheung et al 2013). Similarly, the loss of MITF, a melanocyte differentiation factor, is sufficient to increase metastasis of melanoma (Cheli et al 2012).…”
Section: Cell Fate Determinants As Regulators Of Micsmentioning
confidence: 99%
“…For example, binding of CREB 51 and GADD45B 52 in the BDNF region upstream of the rs6265 SNP has been detected. Moreover, BHLHB2 and GADD45B are regulated by hypoxia, since they have a highstringency HIF1 binding site, 53,54 and BHLHB2 represses expression of MITF, 53 a TF stimulating HIF1a expression. 55 Studies in mice have also proved how the basic helix-loop-helix protein BHLHB2 is regulated by neurotrophins and modulate BDNF transcription.…”
Section: Relationship Between Rs6265 Genotype and Dna-protein Bindingmentioning
confidence: 99%